Odpowiedzi

2010-01-30T16:35:01+01:00
A) 9a -6b
a reszta to trudna ;/ przykro mi ale tylko to wiem
3 2 3
Najlepsza Odpowiedź!
2010-01-30T16:55:45+01:00
A) 3a-4b-6a-2b = -3a-6b
b) 2a-a²+a+a²-3a+4a²b = 4a²b
c) (x-y)+(x+2y) = x-y+x+2y = 2x+y
d) x²-7x+8-2x²+6x+8 (x²-7x+8)-(2x²-6x-8) = -x²-x+16
e) (x-2y)-(-6x+y)-(-6x-y) = x-2y+6x-y+6x+y = 13x-2y
f) 3(x-7) = 3x-21
g) (6x²-2y+3):2 = 3x²-y+1½
h) -(2x²-y+xy)+2(x²-3y-xy) = -2x²+y-xy+2x²-6y-2xy = -5y-3xy

1 5 1
2010-01-30T16:59:47+01:00
A) 3a-4b-6a-2b= -3a+6b
b)2a-a²+a+a²-3a+4a²b= a+ 4a²b
c)(x-y)+(x+2y)= x² + 2xy - xy - 2y²= x² + yx -2y²
d)(x²-7x+8)-(2x²-6x-8)= -x²+7x-8-2x²+6x+8= -3x² + 13x
e)(x-2y)-(-6x+y)-(-6x-y)= -x+2y+6x-y+6x+y= 11x+2y
f)3(x-7)=3x-21
g)(6x²-2y+3):2= 3x² -y+1,5
h)-(2x²-y+xy)+2(x²-3y-xy)= -2x²+y-xy+2x²-6y-2xy= -5y + xy
1 5 1